Commutators of Multilinear Singular Integrals with Lipschitz Functions (Communications in Mathematical Research, 2021)
The boundedness of commutators of multilinear singular integrals withLipschitz functions in product Lebesgue spaces is obtained.
Keywords: multilinear singular integral; Lipschitz function; commutator; maximal function.